Software development practices in small entities: an ISO29110‐based survey. Issue 11 (14th October 2016) - Majchrowski, Annick; Ponsard, Christophe; Saadaoui, Sanae; Flamand, Jacques; Deprez, Jean‐Christophe
Abstract: Small and medium‐sized enterprises (SMEs) involved in software development often experience problems in mastering their development processes. This can lead to time and cost overruns or failure to address functional and nonfunctional requirements. In general, this can significantly affect customer satisfaction and hamper business growth potential. This paper reports on a survey conducted in Belgium to assess more precisely which and how SMEs are affected by problems related to development processes. The survey was driven by the ISO29110 lightweight standard focusing on very small entities developing software, ie, whose internal IT department is less than 25 people. Worldwide, and in particular in Belgium, this represents a very large portion of SMEs in business. Survey results highlight the most frequent issues and how they may be linked to organization and project characteristics. The survey is based on a free online self‐assessment tool. Therefore, results go 1 step further than identifying issues encountered in companies: the tool also infers a set of quick‐win high‐level recommendations to solve these issues. Our results are also compared with those reported by other surveys targeting both large and small companies. Abstract : Small and medium‐sized enterprises involved in software development often experience problems in mastering their development processes. We report on a survey conducted in Belgium to assess which and how SMEs are affected by such problems. The survey was driven by the ISO29110 lightweight standard. It was conducted using an online self‐assessment tool. Survey results highlight the most frequent issues and how they may be linked to organization and project characteristics. It also infers quick‐win recommendations to address them.